1999
DOI: 10.1210/jcem.84.6.5733
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Dysfunction in Patients with Subclinical Hypothyroidism

Abstract: Although subclinical hypothyroidism is frequently diagnosed, the decision to institute a substitutive therapy with L-T4 remains controversial. Because the cardiovascular system is considered a main target for the action of thyroid hormone, we investigated whether subclinical hypothyroidism induces cardiovascular abnormalities. Twenty-six patients (mean age, 36 +/- 12 yr) were evaluated by Doppler-echocardiography, whereas a subgroup of 10 patients, randomly selected, were reevaluated after 6 months of L-T4 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(146 citation statements)
references
References 30 publications
8
124
1
6
Order By: Relevance
“…Some studies of adults with SH showed abnormalities of myocardial function, reversible with L-thyroxine therapy 58 59. A small study of 16 DS children with prolonged SH, showed no difference in myocardial function compared to age and body-surface area matched euthyroid DS controls 60…”
Section: Embryologymentioning
confidence: 99%
“…Some studies of adults with SH showed abnormalities of myocardial function, reversible with L-thyroxine therapy 58 59. A small study of 16 DS children with prolonged SH, showed no difference in myocardial function compared to age and body-surface area matched euthyroid DS controls 60…”
Section: Embryologymentioning
confidence: 99%
“…LV DD develops in several cardiac diseases [30] as well as in extra-cardiac pathologies involving the heart (accumulation diseases as amyloidosis, thyroid disorders, acromegaly and others) [31,32] and in myocardial ischemia due to coronary artery stenosis or even to isolated dysfunction of coronary microcirculation [33]. However, the main cause of DD is arterial hypertension [5-7].…”
Section: Determinants Of Diastolic Dysfunctionmentioning
confidence: 99%
“…There has been a large number of studies which used the conventional analysis method of the mitral Doppler flow (29,43), but also the tissue Doppler evaluation (38,42,44) for the investigation of the LV function at patients with overt and subclinic hypothyroidism. In our study, the diastolic function was affected in both groups as compared to the control group, which is consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 99%